Impact of running techniques through the sprint ability in athletes during the COVID-19 pandemic - Purwanto, P.; Lumintuarso, R.; Burhaein, E. (International Journal of Human Movement and Sports Sciences, 2021)
With the spread of the Covid-19 virus that is increasingly widespread, athletes cannot train optimally. This study aims to determine the effect of sprint running techniques on the ability of the 100-meter sprint in athletes during the COVID-19 pandemic. The method in this study was a true experiment with a pretest-posttest control group design. The total participants were 38 male athletes with an age range of 15-18 years (M = 17.3; SD: 1.26). Data analysis in this study is descriptive analysis and hypothesis testing. The results of the study are: 1) For the control group, the H0 (not significant) statement "There is no effect and difference of sprint running technique on the athlete's 100 meters running ability", is not rejected. Then, there was a decrease in the mean of 0.23 or 1.78%; 2) For the experimental group, the H1( significant) statement "There is an effect of sprint running technique on the athlete's 100-meter running ability during the COVID-19 pandemic", is not rejected. Then supported by an increase in the mean of 0.44 or 3.42%, the conclusion is that there is an effect of sprint running techniques on the ability of the 100-meter sprint in athletes. This finding can have implications, namely being a reference for coaches or teachers in compiling training programs to improve the achievement of the 100-meter sprints in athletic sportsduring the COVID-19 pandemic. Further researchers should be able to modify other types of exercise and conduct research with a wider sample and population and add different variables.